SIMULATOR SISTEM PENENTUAN DAN PENGENDALIAN SIKAP SATELIT UNTUK POINTING KE BINTANG: KASUS BETELGEUSE DAN POLARIS - Khadafi, Muhamad
Satellite simulator is a tool to represent the real conditions of satellites. The simulator is built with MATLAB / Simulink software that can visualize the orbit and attitude of satellites in 2D and 3D. Because satellites operate in space, the influence of the space environment cannot be ignored. To represent the space environment, models of the Earth’s magnetic field and the position of the Sun are used in this simulator. For satellites in LEO (Low Earth Orbit), the influence of the Earth's magnetic field on the satellite is very strong and can be used to determine (with sensors) and control the attitude of satellites (with actuators). In this simulator, the Earth's magnetic field model is based on data from the IGRF-13 (International Geomagnetic Reference Field) which is valid until 2025 and is implemented as a magnetometer sensor. Earth has an atmosphere that serves as a protector for survival on this planet. But as a consequence, not everything can be done perfectly from Earth because of atmospheric turbulence, such as seeing and scintillation when observing stars. The atmosphere cannot be eliminated, so to overcome this problem, satellites that can do pointing to stars can be used to conduct star observations by controlling the attitude in inertial pointing mode. To achieve the desired attitude control mode (de-tumbling or inertial pointing), the PID controller and actuator are used. The actuator used is magnetorquers (electrified coils of wire to produce magnet dipole moments and interacting with the Earth's magnet field to produce torques on satellites). For the orbit propagator, SGP4, where the disturbances from the space environment of the satellite orbit are included, is used. The results obtained in this Final Project are satellite simulators successfully pointing to Betelgeuse with an accuracy of 1o and Polaris with an accuracy of 2o.